(untitled) (Dermatology Reports, 2018)
The differential diagnosis of chronic ulcers covers a wide range of diseases and poses a diagnostic challenge. Subcutaneous ischemic arteriolosclerosis can lead to local ischaemia and ulceration as a result of arteriolar narrowing and reduction of tissue perfusion. This pathophysiological feature can be seen in eutrophication (nonuremic calciphylaxis) in morbid obesity, hypertensive ischemic leg ulcer (Martorell ulcer) and calciphylaxis in chronic renal insufficiency. All of the ulcers happened in this way can be wrongly diagnosed as pyoderma gangrenosum because of clinical similarity and inadequate biopsies. We report a case of chronic ulcer due to subcutaneous arteriolosclerosis in morbid obesity, wrongly diagnosed as pyoderma gangrenosum. It can be detrimental to misdiagnose the ulcers due to subcutaneous arteriolosclerosis as pyoderma gangrenosum since they need a diametrically different approach.